Path-dependent import-substitution policies: the case of Argentina in the twentieth century - Sebastián Galiani; Paulo Somaini (Latin American Economic Review, 2018)
Abstract We use a simple three-sector model to narrate the economic history of Argentina during the twentieth century as seen through the prism of its integration into and dis-integration from the world economy. Assuming that capital moves between the primary and secondary sectors more slowly than labor moves between the secondary and tertiary sectors, we show that import-substitution policies exhibit path dependence. We contend that the endogenous industrialization of the inter-war period generated political changes that paved the way for import-substitution industrialization during the post-war period. Even if this inward-oriented strategy failed to spur economic growth, protectionist policies became entrenched. In the absence of mature political institutions, the liberalization process was delayed and, when it finally did occur, it was extremely costly.